2018
DOI: 10.1007/s41999-018-0139-y
|View full text |Cite|
|
Sign up to set email alerts
|

Older HIV-infected adults: complex patients (III)—polypharmacy

Abstract: Polypharmacy is a well-described problem in the geriatric population. It is a relatively new problem for people living with HIV (PLWH), as this group now has a life expectancy approaching that of the general population. Defining polypharmacy for PLWH is difficult, since the most common traditional definition of at least five medications would encompass a large percentage of PLWH who are on antiretrovirals (ARVs) and medications for other medical comorbidities. Even when excluding ARVs, the prevalence of polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…We defined sPP as the use of 10 or more concomitant medications as in other similar studies 17 : the prevalence was similar between PLWH and controls and this may be explained by a significantly higher proportion of controls falling in the definition of elderly subjects (ie, 65 years old or more).…”
Section: Discussionmentioning
confidence: 99%
“…We defined sPP as the use of 10 or more concomitant medications as in other similar studies 17 : the prevalence was similar between PLWH and controls and this may be explained by a significantly higher proportion of controls falling in the definition of elderly subjects (ie, 65 years old or more).…”
Section: Discussionmentioning
confidence: 99%
“…Important considerations for prescribing ARVs in the context of polypharmacy and aging have been the subject of comprehensive and recent reviews (45). For example, one review discussed the complexities of optimizing cancer treatment in the context of ARVs (46).…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…Given rising rates of opioid overdose deaths among PWH(63), the use of prescribed opioids among PWH warrants specific mention (45). It has been consistently documented that opioid prescribing alone and with other psychoactive medications is widespread among PWH receiving care in diverse settings (64,65).…”
Section: Medication Classes Of Particular Concern Among Pwhmentioning
confidence: 99%
“… 6 In different regions, the prevalence of polypharmacy among older PLWHIV ranges from 15% to 55%. 7 , 8 Because of age-related physiological changes and organ hypofunction, the polypharmacy issue among older PLWHIV becomes complicated with the subsequent risk of potential drug–drug interactions (PDDIs). A cross-sectional study 9 conducted in Spain with PLWHIV aged 65 and above reported that 93% were taking polypharmacy and 65% showed at least one PDDI.…”
Section: Introductionmentioning
confidence: 99%